Invasive Aspergillosis: Epidemiology, Clinical Aspects, and Treatment - Gregg, Kevin S.; Kauffman, Carol A. (Seminars in Respiratory and Critical Care Medicine, 2015)
Invasive aspergillosis remains an often fatal, difficult-to treat infection in immunocompromised patients. Patients not classically defined as immunocompromised, especially those in an intensive care unit setting, also develop invasive aspergillosis. Clinical clues suggesting angioinvasion and radiographic modalities, especially computed tomographic scans, combined with newer non–culture-based diagnostic techniques, have allowed earlier recognition of invasive aspergillosis. Although mortality remains high, it has greatly decreased over the past 15 years. Voriconazole has supplanted amphotericin B, with its various toxicities, as primary treatment for invasive aspergillosis. Combination therapy with voriconazole and an echinocandin for initial therapy, based on results from a recent controlled clinical trial, could become the standard of care in high-risk patients.
Keywords: aspergillosis; Aspergillus fumigatus; voriconazole; echinocandins; amphotericin B; epidemiology; hematopoietic cell transplant; solid-organ transplant